2016
DOI: 10.1097/pcc.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Hematopoietic Stem Cell Transplant and Intensive Care

Abstract: This is the largest single-center series for pediatric patients who require intensive care posthematopoietic stem cell transplant and demonstrates that this group of patients still faces high mortality. There has been an improvement in survival for those patients who require renal replacement therapy and also for patients who require mechanical ventilation more than once; however, the need for mechanical ventilation still remains a significant predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
3
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 15 publications
3
35
3
3
Order By: Relevance
“…In our study, cases and controls had similar rates of intubation for at least four hours pre‐ECMO, and no significant difference in OI. Additional risk factors for mortality in other studies included lower PaO 2 before ECLS, need for inotrope support (non‐ECMO), 13,41,48,49 and duration of ICU admission prior to intubation 44 . However, none of these variables at the time of cannulation were significantly different between cases and controls in our report.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study, cases and controls had similar rates of intubation for at least four hours pre‐ECMO, and no significant difference in OI. Additional risk factors for mortality in other studies included lower PaO 2 before ECLS, need for inotrope support (non‐ECMO), 13,41,48,49 and duration of ICU admission prior to intubation 44 . However, none of these variables at the time of cannulation were significantly different between cases and controls in our report.…”
Section: Discussioncontrasting
confidence: 53%
“…However, undergoing HSCT is confirmed to be a risk factor for mortality among this subset of patients [1,2]. Recent studies have reported that outcomes for these patients have improved over the course of years because of PICU technical advances (eg, noninvasive ventilation [NIV] and high-flow oxygen therapy [HFOT]) and improvements in supportive treatment during HSCT [1,[3][4][5][6]. Nevertheless, the mortality rate is still high, especially when invasive ventilation (IV) and continuous renal replacement therapy are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A proportion of 10-20% of children undergoing haemopoietic stem cell transplantation (HSCT) need to be hospitalized in an intensive care unit (ICU) as a result of life-threatening complications (e.g., pulmonary), infections, or graft-vs-host disease. It has been reported that patients surviving after an ICU admission during the transplantation process have a low survival rate in the long run, particularly if they received prolonged mechanical ventilation (e.g., 36% following ICU discharge) [1]. As a result of this low survival rate and the frailty of many hematology-oncology (HO) patients, ICU teams may consider HSCT with mixed feelings with regards to its necessity and associated concerns.…”
Section: Dear Editormentioning
confidence: 99%